A review of key cytokines based on gene polymorphism in the pathogenesis of pre‐eclampsia. (10th November 2021) - Guan, Chengcheng; Zhao, Fei; Yang, Zhencui; Tang, Qian; Wang, Ling; Li, Xueli; Zhang, Lixia; Deng, Ziwen; Hou, Huabin; Wang, Jingli; Xu, Yinglei; Zhang, Ru; et al.
Abstract: Although a number of theories have been suggested, including roles for oxidative stress, an abnormal maternal‐fetal interface, and genetic and environmental factors, the etiopathology of pre‐eclampsia (PE) remains unclear. Maternal immune tolerance is important for maintaining pregnancy, and researchers have increasingly focused on the critical roles of cytokines in the pathogenesis of PE in recent years. The assessment of candidate genetic polymorphisms in PE could partially elucidate the mechanisms of susceptibility to disease, and contribute to seeking for new diagnosis and treatment methods of PE. PE can lead to severe complications, and even the death of both mother and fetus. Although the complex pathology is not yet clear, some evidence suggested that the occurrence of PE is related to inflammatory factors. We reviewed the current understandings of roles of cytokines in PE, and provided an extensive overview of the role of single nucleotide chain polymorphisms (SNPs) in the genes potentially underlying the pathophysiology of PE.